PENGEMBANGAN MODUL PENGENALAN EMOSI ANAK USIA DINI “YUK KENALI EMOSI KITA” DENGAN MODEL RND - Wahyu Nur Isnaeni; Widyaning Hapsari; Hamas Bernadian (STKIP Subang, 2026)
This study aims to develop an emotional recognition module for early childhoodentitled YUK Kenali Emosi Kita. The module was designed to help childrenrecognize, name, express, and respond to emotions appropriately through concrete,enjoyable, and easy-to-understand learning activities. The novelty of the product liesin the integration of the theories of Vygotsky, Thompson, and Goleman, so that themodule emphasizes not only the introduction of basic emotions but also socialinteraction processes, co-regulation, and the gradual strengthening of children’semotional intelligence. This study employed a Research and Development (R&D)approach using the Borg & Gall model, which was limited to seven stages: (1)identifying potentials and problems, (2) data collection, (3) product design, (4)design validation, (5) design revision, (6) product testing, and (7) product revision.Data analysis techniques used qualitative and descriptive quantitative analysis,while product feasibility was assessed through material expert and media expertvalidation. The validation results showed that the average score from materialexperts was 91.7% in the “Very Good” category, while the average score from mediaexperts was 98.3% in the “Very Good” category. In addition, the product trialobtained a score of 83.3% in the “Good” category. These findings indicate that theYUK Kenali Emosi Kita module is feasible to be used as a supporting learningmedium for emotional recognition in early childhood. The contribution of this studyis the development of an emotional recognition module that is relevant, systematic,and easy for children to understand.